Response of lemon (Citrus limon L.) to foliar spray with organic Optimus Plus and Fe-chelate - Hussein Mohammed Shimran AL-Akaishy; Abbas Mohsen Salman Al-Hamidawi (Kufa Journal for Agricultural Sciences)
The experiment was carried out in the main orchard of the Horticulture Department / Al-Hindiya Station for the production of certified citrus seedlings / Karbala Governorate / Iraqi Ministry of Agriculture, during the 2018 season. The experiment included 9 treatments and three replicates to study the interaction between two factors, The first factor was Optimus plus nutrient solution in three concentrations (0, 1, 2 ml. L-1) which contains (5% nitrogen, 30% amino acid and 3% organic nitrogen) and the second factor was Fe-chelate with three concentrations (0, 500, 1000 mg.L-1). Local lemon grafted on sour were sprayed at a rate of three applications (before sour, month after the last spray). The results showed that spraying with nano-fertilizer Optimus plus at concentration of 2 ml.L-1 and Fe- chelate a concentration of 1000 mg.L-1 resulted in the highest increase in all studied traits including the leaf area, the leaf content of total chlorophyll, and carbohydrates, the number of fruits, fruit weight and total yield, with significant differences compared to the control treatment.